(untitled) (مجلة إحالات, 2026)
Scientific research contributes to catching up with the advanced nations, and the latter is not correct except by the integrity of the researcher and his enjoyment of the morals necessary to carry out his research work. However, we encounter violations that detract from the credibility of the research and affect its results, so we aim behind this study to highlight the ethics and qualities that the researcher should possess when carrying out his research, and to research the various violations that may be committed when editing the research work and to talk about the sensitization and control measures that he introduced The law is for that.